2013
DOI: 10.1007/s10439-013-0867-6
|View full text |Cite
|
Sign up to set email alerts
|

Head Impact Exposure in Youth Football: Elementary School Ages 9–12 Years and the Effect of Practice Structure

Abstract: Head impact exposure in youth football has not been well-documented, despite children under the age of 14 accounting for 70% of all football players in the United States. The objective of this study was to quantify the head impact exposure of youth football players, age 9–12, for all practices and games over the course of single season. A total of 50 players (age = 11.0 ± 1.1 years) on three teams were equipped with helmet mounted accelerometer arrays, which monitored each impact players sustained during pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
178
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 171 publications
(196 citation statements)
references
References 32 publications
15
178
2
1
Order By: Relevance
“…Players between the ages of 9 and 12 years sustained 10.6 impacts per session. 83 A similar dose-response relationship emerged with age and impact magnitudes. Linear magnitudes had median values ranging from 16g to 21g, and angular median values ranged [81][82][83][84]86 from 686 to 1407 rad/s 2 .…”
Section: Normative Datamentioning
confidence: 69%
See 2 more Smart Citations
“…Players between the ages of 9 and 12 years sustained 10.6 impacts per session. 83 A similar dose-response relationship emerged with age and impact magnitudes. Linear magnitudes had median values ranging from 16g to 21g, and angular median values ranged [81][82][83][84]86 from 686 to 1407 rad/s 2 .…”
Section: Normative Datamentioning
confidence: 69%
“…[81][82][83][84]86 Impacts per player per season ranged [81][82][83][84]86 from 161 to 345, with a dose-response relationship of younger athletes sustaining fewer impacts per season. Players between the ages of 9 and 12 years sustained 10.6 impacts per session.…”
Section: Normative Datamentioning
confidence: 99%
See 1 more Smart Citation
“…16,75 However, replication of our results is necessary before using these findings as rationale to implement significant rule or policy changes. Further, it has been suggested that a recent decline in youth sport participation may be attributed, in part, to concerns of parents and guardians about brain trauma.…”
Section: Stamm Et Almentioning
confidence: 77%
“…[6][7][8][9][10] Neuroimaging and electrophysiological studies have identified structural and functional abnormalities in former contact sport athletes many years after they stopped playing. [11][12][13][14][15] Tackle football players ages 7-12 may experience hundreds of repetitive head impacts (RHI), concussive and/or subconcussive, over the course of one season, several of which may exceed forces of 80 g. 16,17 Our previous research suggests that incurring RHI during critical periods of neurodevelopment in childhood may lead to later-life mood, behavioral, and cognitive impairment. 18,19 However, the impact of RHI incurred during youth on later-life brain structure has not yet been systematically examined.…”
Section: Introductionmentioning
confidence: 99%